2000
DOI: 10.1016/s0014-5793(00)01847-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a second site compensatory mutation in the Fe‐protein that allows diazotrophic growth of Azotobacter vinelandii UW97

Abstract: Azotobacter vinelandii UW97 is defective in nitrogen fixation due to a replacement of serine at position 44 by phenylalanine in the Fe-protein [Pulakat, L., Hausman, B.S.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The switch I region in the Fe protein communicates between the nucleotide‐binding site and the docking interface, and previous mutagenesis studies has suggested that residues 59 to 67 are important protein–protein docking interactions 42. In addition, substitution of Av2 Lys170, which has been implicated in interacting with Av1 Glu residues (Table III), gave rise to an inactive Fe protein 43…”
Section: Resultsmentioning
confidence: 99%
“…The switch I region in the Fe protein communicates between the nucleotide‐binding site and the docking interface, and previous mutagenesis studies has suggested that residues 59 to 67 are important protein–protein docking interactions 42. In addition, substitution of Av2 Lys170, which has been implicated in interacting with Av1 Glu residues (Table III), gave rise to an inactive Fe protein 43…”
Section: Resultsmentioning
confidence: 99%
“…In addition to electron transfer, NifH protein performs three more functions. It is involved, along with another seven nif genes, in MoFe cofactor biosynthesis [8,9]. It is also involved in alternative nitrogenase systems regulation.…”
Section: Introductionmentioning
confidence: 99%